Enhancing the Local Community Economy through Financial Transactions: The Contribution of the Rupiah and the Kina - Nani Hanifah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to examine the contribution of the Indonesian Rupiah and the Papua New Guinean Kina in financial transactions and their role in enhancing the local economy in border communities. The research is grounded in the economic phenomenon observed in the Skouw Sae border area, where daily financial transactions are not solely dependent on the national currency but also involve a neighboring country’s currency as an adaptive response to cross-border economic dynamics. A descriptive qualitative approach with a field research design was employed. Data were collected through in-depth interviews, direct observation, and documentation involving local business actors, cross-border traders, and community members engaged in dual-currency transactions. The data were analyzed thematically to identify patterns, mechanisms, and economic implications of dual-currency usage. The findings reveal that the dual-currency financial transaction system contributes positively to transaction intensity, local money circulation, market accessibility, and community purchasing power. Rather than generating economic instability, the use of both currencies functions as an adaptive mechanism that strengthens local economic resilience. This study provides empirical and theoretical contributions to border economy literature and offers policy-relevant insights for designing context-sensitive and inclusive local economic development strategies.